Incidencia de los gastos no deducibles - Impuesto a la Renta de la empresa minera artesanal Mineros Artesanales SAC, Trujillo, 2017 - Uriol Vera, Aurea Janet (2019)
ABSTRACT Expenses Not deductible for tax purposes is a problem that persists for most companies in our country, especially for those companies that do not have trained personnel to face the problem of interpreting and correctly applying the regulatory framework in tax matters, on the other side the tax administration creates limitations and excessive prohibitions that affect the economic situation of companies. This is that, when making the acquisitions of goods, services and the expenses that are part of it, there is no observance of the law or, on the other hand, the norm does not specify the parameters that it establishes, in such a way that it generates the determination of a high tax in favor of the state and unnecessary payments from fines imposed by the SUNAT. For the present investigation, the artisanal mining company Mineros Artesanales SAC, from the city of Trujillo, has been studied. To analyze the incidence of not deductible expenses - Income Tax of the artisanal mining company "Mineros Artesanales SAC", Trujillo, 2017. To test the hypothesis of this explanatory - descriptive study, the design of a transverse non - experimental investigation was selected; interviewed the manager of the company under study; the documentary technique was used and the information was processed with the Excel program. Finally, the research validated the hypothesis; the results show that the factors associated with the non-recognition of expenses for tax purposes in Income Tax are: the lack of a fiscal policy, lack of training of accounting personnel, excess of conditions in the deduction of expenses. In this context, we recommend that the company carry out a tax planning with the objective of managing its expenses avoiding tax contingencies, frequently train its staff on tax issues to reduce tax contingencies, thus optimizing resources.